Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors in Treatment of Metastatic Non-Small Cell Lung Cancer, with a Focus on Afatinib - Morin-Ben Abdallah, Sami; Hirsh, Vera (Frontiers in Oncology, 2017)
First-generation, reversible epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs), erlotinib and gefitinib, represented an important addition to the treatment options for non-small cell lung cancer (NSCLC) patients with activating EGFR mutations. However, all patients inevitably develop acquired resistance to these agents, primarily due to secondary EGFR mutations, molecular aberrations affecting other signaling pathways, or transformation to small cell histology. It was hypothesized that development of second generation TKIs with broader inhibitory profiles could confer longer-lasting clinical activity and overcome acquired resistance to first generation inhibitors. Here, we review the development of afatinib, an irreversible ErbB family blocker that potently inhibits signaling of all homodimers and heterodimers formed by the EGFR, human epidermal growth factor receptor (HER)-2, HER3, and HER4 receptors. In two phase III trials in patients with EGFR mutation-positive NSCLC, first-line afatinib significantly improved progression-free survival (PFS) and health-related quality of life versus standard-of-care chemotherapy. Moreover, in preplanned sub-analyses, afatinib significantly improved overall survival in patients harboring EGFR Del19 mutations. Afatinib has also demonstrated clinical activity in NSCLC patients who had progressed on erlotinib/gefitinib, particularly when combined with cetuximab, and offers ‘treatment beyond progression’ benefit when combined with paclitaxel versus chemotherapy alone. A recent phase III study demonstrated that PFS was significantly improved with afatinib versus erlotinib for the second-line treatment of patients with squamous cell carcinoma of the lung. A phase IIb trial comparing afatinib and gefitinib in first-line EGFR positive NSCLC showed significantly improved PFS with afatinib. The activity of afatinib in both first-line and relapsed/refractory settings may reflect its ability to irreversibly inhibit all ErbB family members. Afatinib has a well-defined safety profile with characteristic gastrointestinal (diarrhea, stomatitis) and cutaneous (rash/acne) adverse events.